Orbital-dependent charge transfer dynamics in conjugated self-assembled monolayers - Hamoudi, Hicham; Neppl, S.; Kao, P.; Schüpbach, B.; Feulner, P.; Terfort, A.; Allara, D.; Zharnikov, Michael (Physical review letters, 2011)
Femtosecond charge transfer (CT) dynamics in a series of self-assembled monolayers with an oligo(phenylenethynylene) and oligo(phenyl) backbone is addressed by resonant Auger spectroscopy using the core hole clock method. The characteristic CT times are found to depend strongly on the character of the molecular orbital (MO) which mediates the CT process. This demonstrates that the efficiency and rate of CT through molecular frameworks can be controlled by resonant injection of the charge carriers into specific MOs.